2015
DOI: 10.2147/ahmt.s69209
|View full text |Cite
|
Sign up to set email alerts
|

A review of mobile applications to help adolescent and young adult cancer patients

Abstract: ObjectiveTo review research articles utilizing mobile applications with adolescent and young adult (AYA) cancer patients.Materials and methodsWe identified articles via online searches and reference lists (eg, PsycInfo, PubMed). Articles were reviewed by two study team members for target population, stated purpose, technological utilization, sample size, demographic characteristics, and outcome data. Strengths and weaknesses of each study were described.ResultsOf 19 identified manuscripts, six met full inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 25 publications
5
84
0
2
Order By: Relevance
“…The following apps, described in the literature, were not available in either app store: Chemotherapy Assistant (CORA), Pain Squad+, Onco‐TreC, Eating After Transplant (EAT! ), Mobile Oncology Symptom Tracker (mOST), and CareZone Cancer . Pain Squad was the only app identified from the literature that was included in MARS scoring.…”
Section: Resultsmentioning
confidence: 99%
“…The following apps, described in the literature, were not available in either app store: Chemotherapy Assistant (CORA), Pain Squad+, Onco‐TreC, Eating After Transplant (EAT! ), Mobile Oncology Symptom Tracker (mOST), and CareZone Cancer . Pain Squad was the only app identified from the literature that was included in MARS scoring.…”
Section: Resultsmentioning
confidence: 99%
“…There exist different types of smartphone applications regarding T2DM self-management, such as “Easy Diabetes”, “Diabetes Manager”, “myDiabetes” and so on[35]. Numerous characteristics of these apps including increased accessibility to educational resources and self-management strategies, more frequent physical and emotional symptom tracking, and increased access to peer support are all main strengths of them in benefiting self-management of individuls[36, 37]. However, there was no previous meta-analysis evaluating the impact of mHealth apps on glycemic control in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although findings have indicated that the performance of these agents still need further improvement, Siri and Google Now will try to promptly communicate to its user of nearby medical facilities or emergency services if the user indicates that they are experiencing some type of physical pain or psychological distress [48]. In addition, as the mHealth field continues to develop, there are future research opportunities to improve the survivorship care of AYA survivors through the use of smartphone apps as this area continues to expand, including through the continued collaborative efforts of both the computer science mHealth and survivorship focused-health services research teams [49]. As technology advances, so do the opportunities to integrate the conversational portion of our SMS system into mobile applications without major user interface and experience changes.…”
Section: Discussionmentioning
confidence: 99%